2015
DOI: 10.1007/s10157-015-1098-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth impairment in children with pre-dialysis chronic kidney disease in Japan

Abstract: This prospective cohort study revealed marked growth impairment in Japanese children with CKD stages 3-5 relative to healthy children. CKD-related risk factors for growth impairment included advanced CKD (stages 4 and 5), being small-for-date, and asphyxia at birth. Growth hormone was infrequently used in this cohort of children with pre-dialysis CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The incidence of CKD in Brunei has shown progressive increments in the ten year period from 2004 to 2013, consistent with trends in the adult population [9] . Local data from the Brunei Dialysis and Transplant Registry revealed a prevalence of 75 pmp in the young adult ESRD (CKD stage 5D) population (age [19][20][21][22][23][24][25][26][27][28][29][30], with a similar trend of increment over the last ten years [10] . If only CKD stage III or lower patients are to be considered, our prevalence of 83 pmcp is on par with data from European studies with similar CKD profiles like Italy (74.7 pmcp) [11] , Belgium (56 pmcp) [12] and Spain …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CKD in Brunei has shown progressive increments in the ten year period from 2004 to 2013, consistent with trends in the adult population [9] . Local data from the Brunei Dialysis and Transplant Registry revealed a prevalence of 75 pmp in the young adult ESRD (CKD stage 5D) population (age [19][20][21][22][23][24][25][26][27][28][29][30], with a similar trend of increment over the last ten years [10] . If only CKD stage III or lower patients are to be considered, our prevalence of 83 pmcp is on par with data from European studies with similar CKD profiles like Italy (74.7 pmcp) [11] , Belgium (56 pmcp) [12] and Spain …”
Section: Discussionmentioning
confidence: 99%
“…This is not unusual for children with CKD due to congenital predisposition, electrolyte imbalances, malnutrition, bone disease and medications [26] . Hamasaki et al [27] revealed that Asian CKD patients with congenital anomalies, lower GFR, being small for date and asphyxia at birth are more likely to have growth impairment. Our research showed that female and adolescent patients are more likely to experience growth attenuation.…”
Section: Tan Sy Et Al Ckd In Children In Bruneimentioning
confidence: 99%
“…3 Our study also found no correlation between nutritional status and several indicators, including age, genders, primary etiological factors, and family economic status, which is consistent with previous studies. 6,7,15,16 The absence of correlation between nutritional status and age could be attributed to other factors influencing the disease. Hogan et al revealed that nutritional status is not related to the age of patient if the patient has already developed CKD before others, supporting the finding.…”
Section: Apghnmentioning
confidence: 99%
“…Наличие любого хроничес кого заболевания может влиять на рост и развитие детей и подростков, приводя к отставанию в росте или дефициту массы тела. Физическое развитие детей с ХБП оценивали многие детские нефрологи на поздних стадиях, то есть при развитии хронической почечной недостаточности [9,10]. При этом у детей выявляли отставание в росте, прогрессирующее по мере развития почечной недостаточности, то есть от 3-й до 5-й стадии ХБП [12,14].…”
Section: теоретическая и клиническая медицинаunclassified